A step further to the correct identification of Ceropegia bulbosa Roxb. in Kachchh, Gujarat, India - Badheka, A. R.; Parmar, M. J.; Jasrai, Y. T. (Journal of the Bombay Natural History Society (JBNHS), 2013)
No Abstract.